Isolation of microfungi from Arctic and Antarctic soils and their identification using ITS, LSU and SSU sequences. - Idid, M.R.; Krishna, A.; Smykla, J.; Alias, S.A. (2014)
This study presents the biodiversity results of microfungi of soils from Arctic and Antarctica. The Arctic soil samples were collected from Hornsund, whereas the Antarctic soils were sampled from King George Island. Warcup's soil plating method was used for fungal cultivation. Fungal species were identified based on ITS, LSU and SSU sequences using BLAST searches and phylogenetic analysis. Based on the ITS barcoding sequences, fungal species Cosmospora sp., To/ypocladium inflafum (Elaphocordyceps subsessilis), Isaria farinosa (Paecilomyces farinosus), Oidiodendron truncatum, Aspergillus pseudodef/ectus, Preussia borealis, Thelebolus sp., and Phialocepha/a sp. were identified only from the Arctic soils. Meanwhile, Penicillium sp., Geomyces sp., Guehomyces pullulans were isolated from both the Arctic and Antarctic soils. Leuconeurospora sp. and Pseudeurotium sp. were isolated only from the Antarctic soils. Although there were limited barcoded species using LSU and SSU sequences in GenBank, some of the species identification corresponded with those of ITS sequences.